Switching Costs, Brand Premia and Behavioral Pricing in the Pharmaceutical Market - Aljoscha Janssen (Research Institute of Industrial Economics (IFN), 2020)
This article examines the market power of branded prescription drugs faced with generic competition. Using prescription-level and matched socioeconomic panel data of the entire Swedish population between 2010 and 2016, I provide evidence for the key role of switching costs. A discontinuity surrounding patent expirations establishes that the effect is causal. Further, by comparing patients with and without medical education, I show that those without medical education experience higher brand premia. A unique feature of the Swedish market allows me to rule out patients' inattention due to information costs as a source of market power. Therefore, switching costs and perceived quality differences are the key determinants of market power. I then estimate a dynamic oligopoly model with forward-looking firms which is used in counterfactual studies of the effect of switching costs and perceived quality differences on prices. First, an increase in the length of procurement mimics a reduction of switching costs and increases prices. While the effect of switching costs on prices in theory is ambiguous, moderate switching costs and sufficient competition for new patients increase competitive pressure. Second, if everyone acts as a medical expert and experiences fewer brand premia, prices decrease.
Keywords: D12; I11; L13; 330; Switching Costs; Brand Premia; Behavioral Pricing; Pharmaceuticals